The unusual mycobacterial chaperonins: evidence for in vivo oligomerization and specialization of function. - Fan, M; Rao, T; Zacco, E; Ahmed, M; Shukla, A; Ojha, A; Freeke, J; Robinson, C; Benesch, J; Lund, P (2012)
The pathogen Mycobacterium tuberculosis expresses two chaperonins, one (Cpn60.1) dispensable and one (Cpn60.2) essential. These proteins have been reported not to form oligomers despite the fact that oligomerization of chaperonins is regarded as essential for their function. We show here that the Cpn60.2 homologue from Mycobacterium smegmatis also fails to oligomerize under standard conditions. However, we also show that the Cpn60.2 proteins from both organisms can replace the essential groEL gene of Escherichia coli, and that they can function with E. coli GroES cochaperonin, as well as with their cognate cochaperonin proteins, strongly implying that they form oligomers in vivo. We show that the Cpn60.1 proteins, but not the Cpn60.2 proteins, can complement for loss of the M. smegmatis cpn60.1 gene. We investigated the oligomerization of the Cpn60.2 proteins using analytical ultracentrifugation and mass spectroscopy. Both form monomers under standard conditions, but they form higher order oligomers in the presence of kosmotropes and ADP or ATP. Under these conditions, their ATPase activity is significantly enhanced. We conclude that the essential mycobacterial chaperonins, while unstable compared to many other bacterial chaperonins, do act as oligomers in vivo, and that there has been specialization of function of the mycobacterial chaperonins following gene duplication.